Endolymphatic sac tumours and von Hippel-Lindau disease – case report, molecular analysis and histopathological characterization - Krzystolik, K.; Cybulski, C.; Sagan, L.; Nowacki, P.; Lubiński, J. (Folia Neuropathologica, 2009)
Endolymphatic sac tumours (ELST) are aggressive papillary tumours of the temporal bone. The name was finally determined after the endolymphatic sac was determined as the site of their origin. They should be considered in patients with tumours eroding the petrous part of the temporal bone, extending to the cerebellopontine angle or other adjacent structures. These very rare tumours in the general population have much higher prevalence in von Hippel-Lindau disease. Hence molecular analysis of the VHL gene should be performed in patients with ELST and their relatives. The purpose of this study is to present a case report, histopathological characterization of endolymphatic sac tumours, their association with von Hippel-Lindau disease and use of molecular analysis.